Waste Sadaqah Movement in Indonesia: Socio-Religious Analysis and Its Implications for Environmental Management - Laksono, Gangsar Edi; Ningrum, Arianti Mutia; Setyowati, Putri Ratna; Wafiroh, Arini Inayatul (ICODEV: Indonesian Community Development Journal, 2025)
The waste problem in Indonesia continues to increase along with population growth and urbanization. One of the innovative programs and a new model of community-based waste management is the waste sadaqah movement. This movement is based on the integration of religious values in waste management. This study aims to evaluate the effectiveness of the waste sadaqah movement in reducing waste and increasing environmental awareness in the community. Through a literature analysis of 24 articles that include journals, proceedings, and community or movement websites, this study found that the waste sadaqah movement succeeded in changing the public's perception of waste from worthless goods to economic and social value resources. This movement has also encouraged community behaviour to be more active in sorting and managing waste and supporting the circular economy. The funds collected from the sale of waste from sadaqah are then used for various social and humanitarian programs that provide tangible benefits to the local community. The results of this study highlight the importance of a religious values-based approach in addressing environmental issues and promoting sustainable development.